THE INFLUENCE OF BPK-RI'S AUDIT FINDINGS IN ORDER TO DETERMINE THE AUDIT OPINION ON THE FINANCIAL STATEMENTS OF THE MINISTRY / INSTITUTION AND THE GENERAL TREASURER OF THE STATE OF THE REPUBLIC OF INDONESIA - Riffo Erlina; Rina Trisnawati; Fatchan Ahyani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to obtain empirical evidence regarding the considerations that determine (Financial Audit Agency of Indonesia) BPK RI's audit opinion on the financial statements of ministries/agencies and the state general treasury. The study was conducted on 84 ministries/agencies and the State General Treasurer whose financial reports have been audited by BPK RI in the 2015 to 2020 financial year, with a research sample of 504 financial statements of ministries/agencies and the State General Treasurer in Indonesia. The analytical method used is ordinal logistic regression. The results showed that the weaknesses of the internal control system were proxied by the number of findings of weaknesses in accounting and reporting controls (SP1) and non-compliance with statutory provisions which were proxied by the number of findings of non-compliance with statutory provisions that resulted in state losses (KP1) had a negative effect on opinion. Audit, while the other criteria for forming an audit opinion have no effect on the audit opinion.